The State of Law : Comparative Perspectives on the Rule of Law in Germany and Vietnam - Alemann, Ulrich von; Baurmann, Michael; Briesen, Detlef; Briesen, Detlef; Cong Giao, Vu; Duc Anh, Pham; Duy Anh, Phan; Haucap, Justus; Khanh, Lai Quoc; Khanh, Lai Quoc; Krüper, Julian; Mengyue, Liu; et al. (düsseldorf university press, 2017)
This book is the result of the first interdisciplinary conference in Vietnam which took place on "the Rule of Law." Instead of beginning immediately with a highly specialized debate from the perspective of one single academic discipline, we started to discuss numerous facets of the subject arising from a multidisciplinary dialogue. For this reason, the contributions for this publication come from various scientific disciplines in Vietnam and Germany: political, historical, social, economic and legal sciences, but also members of Vietnamese governmental and non-governmental organizations. The aim of the volume is to open up a dialogue about the Rule of Law between two very different legal cultures, the German-European and the Vietnamese-Southeast Asian.
Keywords: Rule of law -- Germany.; Rule of law -- Vietnam.; German-European culture.; Rule of Law.; Vietnamese-Southeast Asian culture.; legal culture.; LAW / International.; Rule of law.; Germany.; Vietnam.; Anton-Betz-Stiftung der Rheinischen Post.; Bui Xuan Duc.; Chinese legal institutions.; Chinese social institutions.; Codes of Trust.; Development of Constitutionalism.; Dinh Xuan Ly.; Division and Control of State of Power.; Duong Xuan Ngoc.; Emergence of Market Exchange.; French État legal.; GFFU.; Gerda Henkel Stiftung.; Gesellschaft von Freunden und Förderern der Heinrich-Heine-Universität Düsseldorf.; Global Challenges.; Global Development of Constitutionalism.; Global Governance.; Global Trends.; Heinrich-Heine-Universität Düsseldorf.; Ho Chi Minh's Ideology.; Ho Chi Minh.; Hoang Thi Kim Que.; Human Rights Culture.; Idea of the State of Law.; Julian Krüper.; Justus Haucap.; Legal Pluralism.; Liu Mengyue.; Ly-Tran.; Michael Baurmann.; Montesquieu.; New Institutional Economic Perspective.; Nguyen Ngoc Anh.; Nguyen Thi Chau Loan.; Nguyen Thi Hoi.; Nguyen Thi Thuy Hang.; Pham Duc Anh.; Phan Duy Anh.; Phan Xuan Son.; Police State Vietnam.; Renovation Era.; Rousseau.; Rules of Organization.; Rules of Procedure.; Ruling with Law.; Separation of Powers in Vietnam.; Signs of a State of Law.; Socialist Law-based State.; State of Improvement.; State of Law Indicators.; State of Law in Vietnam.; State of Law.; State of Reformation.; Thomas Schmitz.; Vietnam Communist Party.; Vietnam in the monarchical time.; Vietnam today.; Vietnamese Civil Society.; Vietnamese Legitimate State.; Vietnamese State of Law.; Vietnamese governmental organization.; Vietnamese non-governmental organization.; Vu Cong Giao.; Vu Thi Phung.; Western Political Thought.; anti-corruption.; early Le dynasties.; governing the people.; improving awareness.; policies on governing.; pre-modern Political Thought.; pre-modern separation of powers.; press in Vietnam.; process of improving awareness.; separation of powers.; État legal in Vietnam.; Electronic books.